M-Commerce Role of Device Features towards Intention to Use of - M.F, Shamsudin; Shabi, Khairul Shahida; H.I, Hussain; M.A, Salem (International Journal of Engineering and Technology, 2018)
Community College of QatarInformation Communication and Technology has undergone the spectacular development across the region, which has contributed to the world involvement of information and innovation together with the expansion of massive business growth. The advancement of technology and communication exposed people to vary option of device and facilities experience better daily life. Nowadays, people are becoming familiar with the rapid growth of technology through the usage of Internet and mobile device with better infrastructure. Device feature (DF) also was found to be one of the strongest predictors to use m- commerce among respondents. Device feature is referring to the device technology design characteristics which imply the user intention to adopt m- commerce. It might be because; the users are more concern to use the mobile device with user- friendly specification which allows them to view and experience the m- commerce to the optimum level. The well performed device anticipated to offer a better experience in using m- commerce to the users. As mentioned earlier, the respondents involved are among youngsters or to be specific students where it is anticipated that this group of people who are more exposed to the technology advancement compared to earlier generations. Most of the respondents can be classified as generation Y which might explain to this finding where they concern to have better and suitable device to use m- commerce, which covers on the screen quality, the speed of the device also in term of access quality.